Simple sequence repeat (SSR) vs. sequence-related amplified polymorphism (SRAP) markers for Cynara cardunculus characterization - Casadevall, R.; Martin, E.; Cravero, V. (Spanish Journal of Agricultural Research, 2011)
A little is known about the genetic variability present in globe artichoke, cultivated and wild cardoons. This knowledgeis very important for efficient genetic resources utilization, and to gain a better understanding of genetic structure of thisbotanical varieties. With the aims to determine genetic distances between Cynara cardunculus accessions and to compare two molecular markers systems for their efficiency to differ between botanical varieties, a molecular characterization of sixteen accessions from different geographical origins was performed. Seven SSR and seven SRAP markers were usedfor varieties characterization and to calculate genetic distances between them. Both distance matrices were subjected to cluster analysis. Exclusive SSR alleles were found for globe artichoke and for wild cardoon, but non exclusive alleleswere found for cultivated cardoon. For both markers systems two major groups were identified, one of them includedmostly globe artichoke accessions and the other one grouped mainly cardoons. The differences observed in the sub-clusterconformation with each marker systems may be due to intrinsic characteristics of the markers. Concluding, both kind of molecular markers are valuable tools for studying genetic distances between C. cardunculus accessions although theygive different information. Nevertheless, SSR electrophoretic profiles are simpler to score than SRAP markers becausethey consist of just a few bands. As well, bands are highly informative because of the great number of alleles existing inpopulation and they are codominant markers. In addition, SSR’s use would reduce time and costs.